(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
In 1976 Ludovico Quaroni as a leader of a group of young Roman architects, Maria Angelini, Florindo Fusaro, Ludovico Micara, Attilio Petruccioli, Antonino Terranova, all assistants in his Composition courses, submits a project to the International Competition for the Italian Islamic Cultural Centre and Mosque in Rome. It is a little known project, unpublished in books on Quaroniâ€™s architectural work, due to its relative eccentricity in relation to current interpretations of his architectural thought. The project highlights the profound interest of Ludovico Quaroni for the Islamic cities and culture, mainly Persian, not to be confused with an orientalizing attitude, these cities being also the object of his travels and studies. Another major topic is that of the architectural order, no longer a classic order, as in the first Roman experiences, but a rule which is possible to interpret and transgress in order to create new architectural meanings. It is precisely the theme of the architectural order that brings Quaroni back to his first book, Lâ€™architettura delle cittÃ . Its contents, frequently emerging in his designing activity, define in fact Quaroni as a post-antique architect, as he liked to define himself, instead of post-modern, a label often associated to his project for the Opera House in Rome. Â